The consumer genome: Willingness to share and accept genetic data in marketing - Gil, J. C.; Guerreiro, J. (Electronic Markets, 2025)
Genetic marketing presents novel challenges for marketing, namely how its implementation impacts consumers’ attitudes. The current study is grounded on the privacy calculus and theory of planned behavior theories to understand how consumers are willing to accept the use of genetic data for marketing purposes. A total of 309 consumers were surveyed about their perceptions of using genetic data. The study shows that creating benefits for the disclosure of information, establishing a positive reputation for the organization, and building systems that empower consumers in terms of control over their genetic data will help consumers accept genetic marketing practices.